The Role of the Principal in Improving the Professionalism of Teacher Discipline in Teaching (Case Study at MI Al-Azizy Daleman Karduluk) - Faizun Najah; Robitul Abror (Penerbit Hellow Pustaka, 2025)
This study analyzes the principal's strategy in improving teacher discipline at MI Al-Azizy Daleman Karduluk, a private madrasah with limited facilities. Using a qualitative case study approach, data were collected through interviews, observations, and documentation of the principal and teachers. The results of the study revealed four effective strategies: (1) spiritual motivation based on religious values ​​(